BARRIERS AND FACTORS SUPPORTING AGRITOURISM AND ECO-AGRITOURISM ACTIVITIES IN THE BUG VALLEY MUNICIPALITIES IN THE OPINION OF FARM OWNERS - Katarzyna Radwańska; Dominik Dąbrowski; Janusz Sokół (Acta Scientiarum Polonorum. Oeconomia, 2019)
The objective of the study was to present the barriers as well as factors which, in the opinion of farm owners inhabiting the Bug valley municipalities of the three voivodeships (Lubelskie, Podlaskie and Mazowieckie) support the agritourism and eco-agritourism activities. The result of the survey carried out amongst 99 farm owners, is, among others, a conclusion that from amongst the many barriers in the development of rural tourism, the lack of habit of weekend leisure in potential tourists is the most significant one, whilst the time-consuming and expensive process of transforming the farms into ecological farms, disproportionate towards the profitability of venture is the factor which limits the creation of eco-agritourism farms to the greatest extent. Natural values, quietness and peace prevailing in the vicinity of such farms are the factors which support the development of such activities above all.